1985
DOI: 10.1128/mcb.5.11.3301
|View full text |Cite
|
Sign up to set email alerts
|

Transformation-defective mutant of avian myeloblastosis virus that is temperature sensitive for production of transforming protein p45v-myb.

Abstract: We have characterized a mutant of avian myeloblastosis virus (strain GA907/7) that shows a reduced capacity to transform myelomonocytic cells at the nonpermissive temperature. Myelobiasts transformed by this mutant suffer a substantial decrease in the amount of the transforming protein p45v-myb when shifted from the permissive to the nonpermissive temperature. We presume that the 5-to 10-fold decrease in the amount of p45vmyb causes the loss of the transformed phenotype. The decrease is due to a reduction in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

1986
1986
1990
1990

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
(14 reference statements)
1
5
1
Order By: Relevance
“…By contrast, the surplus of subgenomic mRNA for wtAMV remained similar to that found in transient assays ( Fig. 2B; Table 2) and also resembled the results obtained previously with transformed lines of myeloid cells (10,18). We concluded that transfection under conditions that permit establishment and spread of infection can reproduce the biochemical phenotype of tsAMV in CEF.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…By contrast, the surplus of subgenomic mRNA for wtAMV remained similar to that found in transient assays ( Fig. 2B; Table 2) and also resembled the results obtained previously with transformed lines of myeloid cells (10,18). We concluded that transfection under conditions that permit establishment and spread of infection can reproduce the biochemical phenotype of tsAMV in CEF.…”
Section: Resultssupporting
confidence: 89%
“…The preceding results contrasted sharply with our previous findings for myeloid cells transformed by tsAMV, which contained genomic RNA in substantial excess of the smaller mRNA at either the permissive or the restrictive temperature (18). We speculated that this difference might be due to the use of a transient assay in the present experiments and therefore designed an experimental strategy that addressed this possibility.…”
Section: Resultscontrasting
confidence: 63%
See 3 more Smart Citations